Bimodal magmatism produced by delamination: geochemical evidence from late Palaeozoic volcanic rocks from the Yili Block, Western Tianshan, Northwestern China. (27th June 2021) - Chen, Genwen; Liu, Rui; Deng, Teng; Wang, Lixing
Abstract: The Western Tianshan orogenic belt is essential for understanding the evolution of the Central Asian orogenic belt. However, no agreement exists among geologists about its tectonic environment during the Late Palaeozoic. The volcanic rocks of the Yishijilike and Wulang Formation in the Yili Block, Western Tianshan, formed in the Late Carboniferous to Early Permian, mainly consist of a bimodal suite of basalts – basaltic andesites and rhyolites, with only some intermediate rocks. Mafic rocks are slightly enriched in light rare earth elements (LREE) and depleted in Nb, Ta, Zr and Hf, suggesting a subduction-modiﬁed depleted mantle source. Some mafic samples in the Early Permian bimodal volcanic rocks have high Ti contents with relatively high concentrations of Nb and high field strength elements (HFSE) and low contents of heavy rare earth elements (HREE). These rocks are similar to the continental flood basalts, which suggests that they formed from an asthenospheric mantle. This paper indicates that mafic members were created by the partial melting of the asthenospheric mantle material and subduction-modiﬁed lithospheric mantle mixture. Some rhyolites and dacites in the Wulang formation were enriched in Ga, Nb, Zr, Ce and Y and depleted in Sr and Eu. Additionally, they showed fractionation of rare earth elements (REE) with negative Eu anomalies, which is indicative of an A-type affinity of felsic rocks. The genesis of mafic members and an A-type affinity of felsic members indicate that the Late Carboniferous – Early Permian magmatism in the Western Tianshan area formed as a result of an extensional setting. This study also reveals bimodal magmatism produced by delamination in an extensional tectonic setting.